The Shapes of Fancy Reading for Queer Desire in Early Modern Literature - Varnado, Christine, 1980-; Project Muse. (University of Minnesota Press, 2020)
"The Shapes of Fancy attempts to move the locus of queerness away from individual bodies or persons to scenes, plots, relations, and networks and, in doing so, redefine queer desire as an affective mode" --
Introduction: Reading for Desire -- Getting Used, and Liking It: Erotic Instrumentality and the Go- -- Between -- Everything That Moves: Promiscuous Fancy and Carnival Longing -- It Takes One to Know One: Paranoid Suspicion and the Witch Hunt -- Lost Worlds, Lost Selves: Queer Colonial Melancholia -- Conclusion: The Persistence of Fancy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Queer theory; Affect (Psychology) in literature; Desire in literature; Electronic books